MANAJEMEN PENGEMBANGAN KURIKULUM TERINTEGRASI DEEP LEARNING SEKOLAH DASAR - Bagus Aulia Iskandar; M.Ziyan Takhqiqi Arsyad; Ahmad Riandy Agusta; Arif Rahman Prasetyo; Dede Dewantara; Muhammad Naufal; Annisa Aulia Rahma (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The implementation of the Merdeka Curriculum necessitates a transformative pedagogical approach to bridge the gap in 21st-century competencies. This study aims to analyze curriculum development management that integrates the Deep Learning approach characterized as Mindful, Meaningful, and Joyful at SDIT Ukhuwah, SDN Pasar Lama 1, and MDIM Kindaung Banjarmasin. Utilizing a qualitative approach with a multi-case study design, the research reveals that the integration of Deep Learning is anchored in three key management pillars. First, visionary instructional leadership fosters collective and reflective awareness. Second, teacher empowerment through the granting of autonomy and professional trust cultivates an enthusiastic atmosphere of innovation. Third, strategic partnerships involving parents and the wetland environment ensure contextual and relevant learning. The study concludes that a harmonious synergy among leadership, empowerment, and partnership constitutes a fundamental prerequisite for establishing an adaptive educational ecosystem oriented toward the development of students' holistic competencies.